South West Khasi hills district, Mawkyrwat, Meghalaya (India) landslides’ 2022: Case studies, lesson learned and mitigation measures - Masan, Ebormi S. Langshiang; Langshiang, Ambiangmiki S. (Institute for Advanced Science, Social, and Sustainable Future, 2024)
In June of 2022, a series of landslides occurred in the South West Khasi Hills district of Meghalaya during the monsoon season. These events caused significant damage to roads, PHE pipelines, and agricultural areas, and resulted in the deaths of two people and nine animals. The primary cause of the landslides was the incessant rain; Meghalaya being the wettest place on Earth is particularly vulnerable to landslides due to heavy rainfall and extreme tectonic stress. In addition to these natural elements, the construction of roads and excavation activities would have increased the instability of the slopes and increased the risk of landslides. The paper aims to investigate the causes of landslides brought on by intense rains in different economic development, offer solutions to mitigate the effects of such occurrences, and highlight the valuable lessons that may be learned from this regrettable incident.